2022
DOI: 10.1002/tox.23557
|View full text |Cite
|
Sign up to set email alerts
|

Syringic acid and silymarin concurrent administration inhibits sodium valproate‐induced liver injury in rats

Abstract: Sodium valproate (SV) is a well‐known anti‐epileptic drug, also used to control convulsions, bipolar disorders and migraines. SV has been shown to induce liver toxicity in clinical subjects. Syringic acid (SA), a natural polyphenolic compound has potential antioxidant, anti‐inflammatory and several beneficial effects. Therefore, in this study, we evaluated hepatoprotective effect of SA against SV‐induced liver injury in rats. Wistar rats were treated with SV orally at a dose of 500 mg/kg, once daily, for 14 da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 56 publications
1
6
0
Order By: Relevance
“…Again, in this study, SYAC at all doses tested significantly decreased the serum activities of these enzymes, suggesting its hepatoprotective role against MTC-induced hepatotoxicity in rats. Our findings agree with previously published studies by Okkay et al [ 45 ] who reported the hepatoprotective effect of SYAC against thioacetamide-induced hepatic encephalopathy and Gheena et al [ 46 ] who reported the hepatoprotective effect of concurrent administrations of SYAC and silymarin against sodium valproate-induced liver injury in rats.…”
Section: Discussionsupporting
confidence: 93%
“…Again, in this study, SYAC at all doses tested significantly decreased the serum activities of these enzymes, suggesting its hepatoprotective role against MTC-induced hepatotoxicity in rats. Our findings agree with previously published studies by Okkay et al [ 45 ] who reported the hepatoprotective effect of SYAC against thioacetamide-induced hepatic encephalopathy and Gheena et al [ 46 ] who reported the hepatoprotective effect of concurrent administrations of SYAC and silymarin against sodium valproate-induced liver injury in rats.…”
Section: Discussionsupporting
confidence: 93%
“…Group II (liraglutide group) received daily liraglutide subcutaneous injection (200 μg/kg body weight) dissolved in normal saline for 4 weeks 10,11 . Group III (valproic acid‐treated group) was administrated sodium valproate (500 mg/kg) dissolved in distilled water (0.5 mL) via oral gavage for 2 weeks 12 . Group IV (combined valproic acid & liraglutide treated group) received the previously mentioned valproic acid dose plus liraglutide subcutaneously (200 μg/kg body weight) daily for 2 weeks which was continued for additional 2 weeks after valproic acid administration.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have also shown that both boldine and SIL have antioxidant and membrane stabilizing properties against various drugs and chemical induced liver injuries. [22,48,49] Therefore, it can be stated that boldine could have nullified CCl 4 mediated free radicals and reduced oxidative stress due to its inherent antioxidant and free radical quenching properties.…”
Section: Boldine and Sil Treatments Induced Changes In Inflammatory M...mentioning
confidence: 99%